Palynozonation of Akukwa-2 Well, Anambra Basin: Implications for Age and Paleoenvironment - Apanpa, Kazeem Abidemi; Adeagbo, Olusola Ayoade; Oladimeji, Razak Gboyega; Adesope, Olajumoke Adebukola (European Journal of Applied Sciences, 2023)
Palynological examination of twenty (20) ditch shale samples from sedimentary succession penetrated by Akukwa-2 Well at depth interval of 3,296 - 3,850 m was undertaken to investigate the occurrence of Palynomorph in the sediments of Anambra Basin with a view to determining the age of the sediments and reconstruct the depositional paleoenvironment. Standard Palynological procedure was followed and the samples were processed using the conventional acid maceration, alkali treatment and staining methods. The oxidized residues were sieved with 5micron nylon sieves using digital Sonifier 450 machine and mounted on glass slides with Norland adhesive gel. Laborlux 12 (Ernst Leitz) transmitting light microscope was used for identification and counting or the palynomorphs. The palynological analysis was done using the population and species of pollen grains, spores and dinoflagelate. The analyzed palynological slides yielded forty nine (49) palynomorphs species identify in the ditch samples, forty (40) were Miospores (pollen and spores) and nine were Dynocysts. However, some diagnostic forms that are stratigraphically useful are present and are used for the palynozonation. Delineation of the well section produced three main palynological zones based on stratigraphic distribution. Zone 1 characterized by the quantitative base appearance of Triorites Africaensis Assemblage indicating Marginal Marine paleoenvironment and of Turonian age; Zone 2, marked by Droseridites Senonicus assemblage also of Marginal Marine but of Coniacian age, Zone 3, marked by Milfordia spp. Acme Zone, purely Marine and of Campano- Maastrichtian age. The study further reveled that Palynomorph recovery in Akukwa-2 well was not that impressive both in terms of abundance and preservation. In most cases, the macerals present seems to indicate high geothermal effect suggesting that some of the kerogen might have been overcooked to imply inability to generate hydrocarbon or such generated hydrocarbon have turned into carbon.